2020
DOI: 10.3390/molecules25102350
|View full text |Cite
|
Sign up to set email alerts
|

Antiadipogenic Effects of Mixtures of Cornus officinalis and Ribes fasciculatum Extracts on 3T3-L1 Preadipocytes and High-Fat Diet-Induced Mice

Abstract: Medicinal plants have been used worldwide as primary alternative healthcare supplements. Cornus officinalis (CO) and Ribes fasciculatum (RF) are traditional medicinal plants applied in East Asia to treat human diseases such as hepatitis, osteoporosis, oxidative stress and allergy. The aim of this study was to examine the anti-obesity effect of CO and RF on preadipocyte 3T3-L1 cells in vitro and high-fat diet (HFD)-induced obesity mice in vivo. Combination treatment of CO and RF in differentiated 3T3-L1 cells i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 49 publications
3
20
0
Order By: Relevance
“…There have been some studies exploring the pharmacological effects and the corresponding mechanisms of herb pairs containing C. officinalis. For example, studies showed that the mixed extract of C. officinalis and Morus alba root and bark could alleviate Osteoarthritis (OA) symptoms of arthroedema, pain and limping, and suppress the expressions of inflammatory markers TNF-α and MMP-13 in the articular cartilage (Park et al, 2020c); the mixture of C. officinalis and Ribes fasciculatum could ameliorate HFD-induced obesity in C57BL/6J mice, reduce the body fat, decrease the fatty deposition in hepatocytes, and suppress the expressions of adipogenesis-associated genes CCAAT/Cebpa, Fabp4, Pparg, and Srebp1 compared with the model mice (Park et al, 2020d). However, these studies only confirmed that the combination of different herbal medicines could enhance the original pharmacological effects, but did not reflect the synergistic mechanism or the side effects antagonistic mechanism between them.…”
Section: Discussionmentioning
confidence: 99%
“…There have been some studies exploring the pharmacological effects and the corresponding mechanisms of herb pairs containing C. officinalis. For example, studies showed that the mixed extract of C. officinalis and Morus alba root and bark could alleviate Osteoarthritis (OA) symptoms of arthroedema, pain and limping, and suppress the expressions of inflammatory markers TNF-α and MMP-13 in the articular cartilage (Park et al, 2020c); the mixture of C. officinalis and Ribes fasciculatum could ameliorate HFD-induced obesity in C57BL/6J mice, reduce the body fat, decrease the fatty deposition in hepatocytes, and suppress the expressions of adipogenesis-associated genes CCAAT/Cebpa, Fabp4, Pparg, and Srebp1 compared with the model mice (Park et al, 2020d). However, these studies only confirmed that the combination of different herbal medicines could enhance the original pharmacological effects, but did not reflect the synergistic mechanism or the side effects antagonistic mechanism between them.…”
Section: Discussionmentioning
confidence: 99%
“…Combined treatment of CO and RF has become well-known traditional herbal agents during the past decade. Previous studies showed that combined CO and RF extracts had synergistic effects on anti-menopausal syndrome and anti-obesity [ 26 , 27 ]. CO and RF mixture decreased adipocyte differentiation in 3T3-L1 pre-adipocytes, through the downregulation of adipogenic markers such as Adipoq , Fabp4 , Pparg , Srebp1 , and Plin1 [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that combined CO and RF extracts had synergistic effects on anti-menopausal syndrome and anti-obesity [ 26 , 27 ]. CO and RF mixture decreased adipocyte differentiation in 3T3-L1 pre-adipocytes, through the downregulation of adipogenic markers such as Adipoq , Fabp4 , Pparg , Srebp1 , and Plin1 [ 26 , 27 ]. Differentiation of adipocyte is characterized by lipid accumulation [ 33 ], CO and RF mixture also inhibited the number of lipid droplets in the cytoplasm of 3T3-L1 cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations